Mozambique | Tropical Cyclone Eloise Response Situation Report #1 | 25 January - 12 February 2021 - Mozambique
English Situation Report on Mozambique about Camp Coordination and Camp Management, Health, Epidemic, Flood and more; published on 12 Feb 2021 by IOM
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; GP - Sofala; L - english / inglês; natural disasters / desastres naturais

Water Warning: The Looming Threat of the World’s Aging Dams (Yale E360)
Tens of thousands of large dams across the globe are reaching the end of their expected lifespans, leading to a dramatic rise in failures and collapses, a new UN study finds. These deteriorating structures pose a serious threat to hundreds of millions of people living downstream.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - central / centro; GP - Tete; L - english / inglês; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura; natural disasters / desastres naturais